Pedagogic Discourse - Tallapessy, Albert (Jurnal Pengembangan Pendidikan, 2011)
Abstract. This paper deals with the theoreticalconstruct of pedagogic discourse. The discourse which focuses greatly onlinguistic aspect of pedagogy is Bernsteinâs long journey of finding thefailure in education. His attention on linguistic aspect was responded by anumber of Systemic Functional Linguists to collaborate Systemic FunctionalLinguistic (SFL) with his theories on code, and later on pedagogic discourse.His idea on regarding linguistic aspect in transmiting knowlde is of a greatcontribution in the study of language and pedagogy.Â Key words: pedagogic discourse, SystemicFunctional Linguistics